RESEARCH PATTERNS ON EARLY CAREER: A BIBLIOMETRIC ANALYSIS - Muhammad Aiman Arifin; Razlina Razali; Ummu Athilia Kamal (International Journal of Accounting, Finance and Business, 2023)
The rapid growth of interest in understanding early career (EC) employee requirements has led to the evolution of research perspectives in the field of human resource management (HRM). HRM scholars in the field of career management are constantly exploring how HRM can develop EC employees via effective practices. However, a comprehensive review of EC employees using bibliometric analysis has not been published. Given this gap, this bibliometric analysis utilized VOS Viewer, Bibliometric R-package, and Map Chart software to evaluate EC employee-related publications, using data extracted from Scopus. 675 documents were studied on EC employee scholarship. This study aimed to analyse (1) volume; (2) increasing trend; (3) worldwide distribution; (4) key journals; (5) pioneer authors; and (6) dominating nations in EC. To achieve this, a specific combination of the words was merged together with logical operators, “TITLE-ABS-KEY (“early career”), thus making the outcomes more centralized. Scholars in the years 2020, 2021, and 2022 showed growing interest in this field, as evidenced by the increasing popularity of publications. Among a total of 675 documents, 322 were published during this period. The analysis showed that the EC is still an emerging concept and this review shall serve as a guide for future research directions by providing a comprehensive overview of the recent development.